Chronic pain after open inguinal hernia repair: expertise-based randomized clinical trial of heavyweight or lightweight mesh. Issue 2 (28th December 2020) - Rutegård, M; Lindqvist, M; Svensson, J; Nordin, P; Haapamäki, M M
Abstract: Background: There is a shortage of high-quality studies regarding choice of mesh in open anterior inguinal hernia repair in relation to long-term chronic pain. The authors hypothesized that heavyweight compared with lightweight mesh causes increased postoperative pain. Methods: An RCT was undertaken between 2007 and 2009 at two sites in Sweden. Men aged 25 years or older with an inguinal hernia evaluated in the outpatient clinic were randomized in an unblinded fashion to heavyweight or lightweight mesh for open anterior inguinal hernia repair. Data on pain affecting daily activities, as measured by the Short-Form Inguinal Pain Questionnaire 9–12 years after surgery, were collected as the primary outcome. Differences between groups were evaluated by generalized odds and numbers needed to treat. Results: A total of 412 patients were randomized; 363 were analysed with 320 questionnaires sent out. A total of 271 questionnaires (84.7 per cent) were returned; of these, 121 and 150 patients were in the heavyweight and lightweight mesh groups respectively. Pain affecting daily activities was more pronounced in patients randomized to heavyweight versus lightweight mesh (generalized odds 1.33, 95 per cent c.i. 1.10 to 1.61). This translated into a number needed to treat of 7.06 (95 per cent c.i. 4.28 to 21.44). Two reoperations for recurrence were noted in the heavyweight mesh group, and one in the lightweight mesh group. Conclusion: A large-pore lightweight mesh causes significantly less pain affecting daily activities a decade after open anterior inguinal hernia repair. Registration number: NCT00451893 (http://www.clinicaltrials.gov ). Abstract : This expertise-based, parallel-group RCT regarding choice of mesh in open anterior inguinal hernia repair in relation to long-term chronic pain was undertaken between 2007 and 2009. Some 271 patients were analysed. Pain affecting daily activities was more pronounced in patients who had surgery with heavyweight versus lightweight mesh (generalized odds 1.33, 95 per cent c.i. 1.10 to 1.61). This translated into a number needed to treat of 7.06 (95 per cent c.i. 4.28 to 21.44). Long term outcomes